Embodied understanding - Johnson, Mark (Frontiers in Psychology, 2015)
Western culture has inherited a view of understanding as an intellectual cognitive operation of grasping of concepts and their relations. However, cognitive science research has shown that this received intellectualist conception is substantially out of touch with how humans actually make and experience meaning. The view emerging from the mind sciences recognizes that understanding is profoundly embodied, insofar as our conceptualization and reasoning recruit sensory, motor, and affective patterns and processes to structure our understanding of, and engagement with, our world. A psychologically realistic account of understanding must begin with the patterns of ongoing interaction between an organism and its physical and cultural environments and must include both our emotional responses to changes in our body and environment, and also the actions by which we continuously transform our experience. Consequently, embodied understanding is not merely a conceptual/propositional activity of thought, but rather constitutes our most basic way of being in, and engaging with, our surroundings in a deep visceral manner.